Value of CEA level determination in gallbladder bile in the diagnosis of liver metastases secondary to colorectal adenocarcinoma - Moura, Rita Maria Aparecida Monteiro; Matos, Délcio; Galvão Filho, Mário Mello; D’Ippólito, Giuseppe; Sjzenfeld, Jacob; Giuliano, Lídia Maria (São Paulo Medical Journal, 2001)
CONTEXT: The relevance of colorectal adenocarcinoma lies in its high incidence, with the liver being the organ most frequently affected by distant metastases. Liver metastases occur in 40 to 50% of patients with colorectal adenocarcinoma, accounting for approximately 80% of deaths in the first three postoperative years. Nevertheless, despite this, they are occasionally susceptible to curative treatment. OBJECTIVE: The present investigation focused on the relationship between the level of carcinoembryonic antigen (CEA) in gallbladder bile and the presence of liver metastases secondary to colorectal adenocarcinoma. DESIGN: Diagnostic test study. SETTING: Surgical Gastroenterology Discipline at the São Paulo Hospital, São Paulo, Brazil. SAMPLE: Forty-five patients with colorectal adenocarcinoma were studied, 30 without liver metastases (group I), and 15 with liver metastases (group II). Diagnosis of liver metastases was made through computed tomography, magnetic resonance imaging and computed tomography during arterial portography. Samples of peripheral blood, portal system blood, and gallbladder bile were collected from patients during the surgical procedure. A control group composed of 18 organ donors underwent the same material collection procedures. CEA level determination was made through fluoroimmunoassay. RESULTS: Mean CEA value in peripheral serum was 2.0 ng/ml (range: 0.7 to 3.8 ng/ml) in the control group, 11.4 ng/ml (range: 0.5 to 110.3 ng/ml) in group I, and 66.0 ng/ml (range: 2.1 to 670 ng/ml) in group II. In the portal system, serum mean values found were 1.9 ng/ml (range: 0.4 to 5.0 ng/ml) in the control group, 15.3 ng/ml (range: 0.8 to 133.3 ng/ml) in group I, and 70.8 ng/ml (range: 1.8 to 725 ng/ml) in group II. Mean values found in gallbladder bile were 4.1 ng/ml (range: 1.0 to 8.6 ng/ml) in the control group, 14.3 ng/ml (range: zero to 93.0 ng/ml) in group I, and 154.8 ng/ml (range: 14.0 to 534.7 ng/ml) in group II. CONCLUSIONS: The CEA level in gallbladder bile is elevated in patients with liver metastases. Determination of CEA both in peripheral serum and in gallbladder bile enabled patients with liver metastases to be distinguished from those without such lesions. The level of CEA in gallbladder bile, however, seems to lead to a more accurate diagnosis of liver metastases secondary to colorectal adenocarcinoma.